2021
DOI: 10.3390/md20010005
|View full text |Cite
|
Sign up to set email alerts
|

Polyketide Derivatives, Guhypoxylonols A–D from a Mangrove Endophytic Fungus Aspergillus sp. GXNU-Y45 That Inhibit Nitric Oxide Production

Abstract: Four undescribed compounds, guhypoxylonols A (1), B (2), C (3), and D (4), were isolated from the mangrove endophytic fungus Aspergillus sp. GXNU-Y45, together with seven previously reported metabolites. The structures of 1–4 were elucidated based on analysis of HRESIMS and NMR spectroscopic data. The absolute configurations of the stereogenic carbons in 1–3 were established through a combination of spectroscopic data and electronic circular dichroism (ECD). Compounds 1–11 were evaluated for their anti-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 17 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…The genus Aspergillus is omnipresent among almost all ecosystems even the circumpolar maritime regions [ 1 ]. Previous investigations on Aspergillus genus indicated that it was rich in bioactive secondary metabolites with multifarious and intricate structures such as sesquiterpenoids [ 2 , 3 ], meroterpenoids [ 4 , 5 ], alkaloids [ 6 , 7 ], and polyketides [ 8 ]. Some of the natural products isolated from Aspergillus genus possessed cytotoxic, antimicrobial, acetylcholinesterase inhibitory, and PTP1B enzyme inhibitory activities [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ], which have attracted great interest of natural chemists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Aspergillus is omnipresent among almost all ecosystems even the circumpolar maritime regions [ 1 ]. Previous investigations on Aspergillus genus indicated that it was rich in bioactive secondary metabolites with multifarious and intricate structures such as sesquiterpenoids [ 2 , 3 ], meroterpenoids [ 4 , 5 ], alkaloids [ 6 , 7 ], and polyketides [ 8 ]. Some of the natural products isolated from Aspergillus genus possessed cytotoxic, antimicrobial, acetylcholinesterase inhibitory, and PTP1B enzyme inhibitory activities [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ], which have attracted great interest of natural chemists.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations on Aspergillus genus indicated that it was rich in bioactive secondary metabolites with multifarious and intricate structures such as sesquiterpenoids [ 2 , 3 ], meroterpenoids [ 4 , 5 ], alkaloids [ 6 , 7 ], and polyketides [ 8 ]. Some of the natural products isolated from Aspergillus genus possessed cytotoxic, antimicrobial, acetylcholinesterase inhibitory, and PTP1B enzyme inhibitory activities [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ], which have attracted great interest of natural chemists. Bisabolanes, a class of sesquiterpenoids possessing diverse skeletons including aromatic monomers and their home/hetero-dimers, are mainly distributed in plant kingdom, marine-derived animals, and fungi [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, more than 1400 new secondary metabolites produced by mangrove-derived fungi have been reported, including polyketides, alkaloids, terpenes and so on, and more than 40% of secondary metabolites displayed cytotoxic, antibacterial and insecticidal activities etc. [3][4][5][6][7][8]. Among them, isocoumarins are lactone-type derivatives derived from the polyketide pathway [9,10], and they possess a wide range of pharmacological activities such as antibacterial 7-hydroxyoospolactone and parapholactone [11], anti-inflammatory (±)-prunomarin A [12], cytotoxic lunatinin [13], insecticidal peniciisocoumarins A and B, antiplasmodial monocerin [14], antioxidant and α-glucosidase inhibitory penicimarin N [15], brine shrimp (Artemia salina) lethal and broad-spectrum antimicrobial penicimarins G-K [16,17], penicoffrazins B and C [18].…”
Section: Introductionmentioning
confidence: 99%
“…1 H NMR (CDCl 3 , 400 MHz): δ H 6.99 (1H, d, J = 8.8 Hz H-6),6.79 (1H, d, J = 8.8 Hz, H-7), 4.26 (1H, m, H-3), 3.83 (1H, m, H-4 ), 3.10 and 2.63 (2H, m, H-4), 1.90 (2H, m, H-1 ), 1.70 (2H, m, H-2 ), 1.50 (2H, m, H-3 ), 1.21 (3H, d, J = 6.0 Hz, H-5 );13 C NMR (CDCl 3 , 100 MHz): δ C 163.3, 159.4, 151.5, 145.1, 135.0, 128.5, 121.2, 111.4, 68.2, 56.6, 39.1, 34.9, 28.0, 23.8, 21.4; ESI-MS m/z 281.1 [M + H] + . (S)-MTPA ester of 1a: 1 H NMR (CDCl 3 , 600 MHz): δ H 7.29 (1H, d, J = 9.0 Hz, H-6), 6.94 (1H, d, J = 9.0 Hz, H-7), 5.12 (1H, m, H-4 ), 4.21 (1H, m, H-3), 2.64 and 2.49 (2H, m, H-4), 1.86 (2H, m, H-1 ), 1.67 (2H, m, H-2 ), 1.55 (2H, m, H-3 ), 1.25 (3H, d, J = 6.6 Hz, H-5 ); ESI-MS m/z 758.2 [M + Na] + .…”
mentioning
confidence: 99%
“…We have reported the isolation of a series of new compounds from the mycelial extract of mangrove endophytic fungi isolated from Acanthus ilicifolius L., such as 2-hydroacetoxydehydroaustin, asperlactone A, and guhypoxylonols A–D [ 8 , 9 , 10 , 11 ]. In our chemical investigation of this fungus, Aspergillus sp., GXNU-A1, a new phenyl R -furopyridone derivative 1 , with four known metabolites 2 – 5 , is discovered ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%